Assessment of Current Mental Health Status in a Population-Based Sample of Canadian Men With and Without a History of Prostate Cancer Diagnosis: An Analysis of the Canadian Longitudinal Study on Aging (CLSA) - Moodie, Louise; Ilie, Gabriela; Rutledge, Robert; Andreou, Pantelis; Kirkland, Susan (Frontiers in Psychiatry, 2020)
Background: Small scale studies indicate an increase in mental health disorders among prostate cancer survivors compared to the general population but large population-based data assessing this relationship are scarce. The present study examined the prevalence of lifetime history of prostate cancer in a cross-sectional sample of Canadian men and assessed the contribution of lifetime history of a prostate cancer diagnosis, multimorbidity, and current alcohol and smoking status to the association with current mental health outcomes in this population. Methods: The analytical sample included 25,183 men (aged 45 to 85 years old) which completed a survey as part of the Canadian Longitudinal Study on Aging (CLSA). The Center for Epidemiological Studies Depression Scale (CES-D10), Kessler’s Psychological Distress Scale (K10) and self-reported mental health were mental health outcomes. Multiple logistic regression analyses, controlling for the complexity of the design and covariates, evaluated the association between prostate cancer survivorship, multimorbidity, alcohol and smoking status, and current mental health outcomes. Results: The prevalence of lifetime history of prostate cancer diagnosis in this population based sample of men was 4% (95% CI: 3.7, 4.4). Our results indicate statistically significantly higher odds of current psychological distress (aOR=1.52,95%CI:1.09,2.11) and screening positive for depression (aOR=1.24;95% CI:1.02,1.51) among survivors of prostate cancer, compared to men without a history of prostate cancer diagnosis in demographics controlled analyses. After addition of multimorbidity and substance use the odds of screening positive for depression among survivors of prostate cancer are 1.32 (95% CI: 1.06, 1.64) higher compared to men who never had a history of prostate cancer diagnosis. Interpretation: Patient education and empowerment programs aimed at addressing concerns during diagnosis and treatment, as well as enhancing survivorship care plans by adding routine screening for mental distress to help survivors overcome poor mental health during the cancer survivorship journey, are warranted.